STRATEGI MENINGKATKAN PENJUALAN PRODUK KULIT KEMBANG TAHU TAWAR DESA RANCA KALAPA TANGERANG MELALUI DIGITALISASI MARKETING - Abdul Rachman Abdul; Muhammad Fajar Ash Shidiqi; Sri Tamara Devy; Tresya Meilina; Siti Nur Afifah; Widi Astuti; Silvi Octavani; Sari Wulandari; Vanny Nurhanifah; Muhammad Rizky Asrof; Ninis Meliyana Putri; Zahra Syafinatunnisa; Siti Nurmila Sari; Nila Hikma Karmelia (Universitas Mataram, 2023)
The role of MSE business actors is very important in increasing regional economic growth so they are obliged to make many creations and innovations for their products so that they can compete regionally and globally. One of the MSME actors who need to innovate and be creative is the Kulit Kembang Tahu Tawar business actor in Ranca Kalapa Village, Panongan, Tangerang Regency. These business actors still produce, package, and market products in a traditional way so that they cannot compete globally. This service activity aims to assist business actors living in Ranca Kalapa, Tangerang, in increasing the selling value of Kulit Kembang Tahu Tawar Products, which are traditional foods, so that they can provide added value to the product and become one of the strategies to increase good sales offline or online. The method used in this activity is PAR (Participatory Action Research). Through this method, the researchers carried out creations and innovations on the skin of fresh tofu cassava by re-branding, re-packing, and re-promoting (digital marketing) so that the resulting product has added value compared to the previous product. The results of this community service activity are new logo designs, new packaging designs, more innovative product packaging, and digital marketing through the Shopee marketplace for Kulit Kembang Tahu Tawar Products so that businesses can increase product sales online.